In vivo cation transport during short-term and long-term digoxin therapy. - Boon, N; Pugh, SE; Hallis, K; Aronson, J; Grahame-Smith, D (1986)
We have studied the effects of digoxin on cation transport in vivo by measuring the changes in plasma and red cell rubidium concentrations following an oral load of rubidium chloride. In eight patients who had been taking digoxin for 7 to 10 days (mean plasma digoxin concentration 1.3 ng ml-1) the rise in plasma rubidium concentrations was enhanced and the rise in red cell rubidium concentrations was attenuated following the oral load of rubidium chloride, by comparison with the changes in well-matched controls. In contrast, the disposition of rubidium was not altered in 12 patients who had been taking digoxin for more than 3 months (mean plasma digoxin concentration 1.1 ng ml-1). These results suggest that the inhibitory effects of digoxin on cation transport are detectable in vivo during short-term therapy, but not during long-term therapy, and confirm our previous in vitro findings.